Physical Component Analysis of Smash Ability in Volleyball Game - Karim, Achmad; Hasbillah, Muhammad; Herman, Herman; Arham, Sarifuddin; Asri, Ariana (Universitas Majalengka, 2025)
This study aims to determine; (1) Is there a relationship between eye-hand coordination and smash ability; (2) Is there a relationship between arm muscle explosive power and smash ability; (3) Is there a relationship between arm muscle strength and smash ability; (4) Is there a simultaneous relationship between eye-hand coordination, arm muscle explosive power, arm muscle strength and smash ability. The population of this study was all male students of SMKN 1 Makassar. The sample used was 30 people. The sampling method used a simple random sampling technique where the sample was taken randomly. The data analysis techniques used in this study were descriptive analysis, correlation analysis, and regression analysis at a significance level of α = 0.05. The results of the study showed that; (1) There is a relationship between eye-hand coordination and smash ability with a value of r = 0.770 (P <α = 0.05). (2) There is a relationship between arm muscle explosive power and smash ability with a value of r = 0.830 (P <α = 0.05). (3) There is a relationship between arm muscle strength and smash ability with an r value of 0.803 (P < α = 0.05). (4) There is a significant relationship between hand-eye coordination, arm muscle explosive power, arm muscle strength and smash ability with an R value of 0.736 or 73.60%.